2021
DOI: 10.5005/jp-journals-10071-23874
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Prognostic Utility of Cellular Components of Hematological System in Sepsis

Abstract: A bstract Background Data are lacking on the role of cellular components of hematological system as biomarkers for prognosis of sepsis. We planned to identify if these parameters measured at admission to ICU and at 72 hours can be useful as prognostic marker in septic critically ill patients. Materials and methods In this prospective observational study, 130 adult patients with sepsis were recruited. Various hematological study parameters (tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…However, only one study explored the role of basophils in patients with sepsis. The authors showed that septic critically ill patients with decreased basophil count at admission to ICU had an increased mortality risk [57].…”
Section: Basophilsmentioning
confidence: 99%
“…However, only one study explored the role of basophils in patients with sepsis. The authors showed that septic critically ill patients with decreased basophil count at admission to ICU had an increased mortality risk [57].…”
Section: Basophilsmentioning
confidence: 99%
“…Similarly, Sinha et al. discovered that platelet count on the first day of admission could predict 28-day mortality in sepsis patients ( 32 ). However, these studies were limited to specific sepsis infections or excluded conditions such as hematological disorders and cancer, which are common complications of cancer treatment ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“… 10 This is similar to other studies performed on critically ill patients. 5 , 6 , 10 This led us to conclude that measuring vitamin D levels before supplementation would not translate to pragmatic ICU practice. Secondly, there have been reports in the literature that the serum vitamin D levels are subject to diurnal variations and a single random value may not be representative of the actual picture.…”
Section: Discussionmentioning
confidence: 99%
“…As per the database of the past 2 years of sepsis patients in our ICU, the mean length of ICU stay was 10 ± 4 days. 6 Considering a decrease in ICU stay of 2 days in the intervention group to be significant, the sample size calculated with a confidence interval of 95%, 80% power of the study and a 1:1 enrolment ratio for intervention and placebo was 126 with 63 in each group. Statistical analysis was performed using SPSS 26.0 (IBM Corp, USA) It was performed based on the intention to treat principle.…”
Section: Ethodsmentioning
confidence: 99%
See 1 more Smart Citation